The Role of Legal Theory in Developing Legal Analysis - S. Sarmawati; Sri Amelia Zulfikar; Mira Nila Kusuma Dewi; A. Aswar; Andy Eko Nugroho; D. Dermawan (Golden Ratio of Data in Summary, 2026)
Legal theory plays a crucial role in the development of juridical analysis, as it enables a deeper understanding of legal concepts and principles, as well as their application in addressing existing legal issues. Legal theory provides the foundational framework for the evaluation and interpretation of law within a broader social context, linking legal norms with the realities of societal life. This journal aims to examine how legal theory contributes to the development of juridical analysis and its impact on the evolution of law in Indonesia. By analyzing the relationship between legal theory and legal practice, this study seeks to offer insights into how legal theory can be applied to formulate solutions to emerging legal problems.